Multifunctional Solar Waterways: Plasma‐Enabled Self‐Cleaning Nanoarchitectures for Energy‐Efficient Desalination. Issue 30 (19th June 2019) - Wu, Shenghao; Xiong, Guoping; Yang, Huachao; Gong, Biyao; Tian, Yikuan; Xu, Chenxuan; Wang, Yan; Fisher, Timothy; Yan, Jianhua; Cen, Kefa; Luo, Tengfei; Tu, Xin; et al.
Abstract: Evaporating seawater and separating salt from water is one of the most promising solutions for global water scarcity. State‐of‐the‐art water desalination devices combining solar harvesting and heat localization for evaporation using nanomaterials still suffer from several issues in energy efficiency, long‐term performance, salt fouling, light blocking, and clean water collection in real‐world applications. To address these issues, this work devises plasma‐enabled multifunctional all‐carbon nanoarchitectures with on‐surface waterways formed by nitrogen‐doped hydrophilic graphene nanopetals (N‐fGPs) seamlessly integrated onto the external surface of hydrophobic self‐assembled graphene foam (sGF). The N‐fGPs simultaneously transport water and salt ions, absorb sunlight, serve as evaporation surfaces, then capture the salts, followed by self‐cleaning. The sGF ensures effective thermal insulation and enhanced heat localization, contributing to high solar‐vapor efficiency of 88.6 ± 2.1%. Seamless connection between N‐fGPs and sGF and self‐cleaning of N‐fGP structures by redissolution of the captured salts in the waterways lead to long‐term stability over 240 h of continuous operation in real seawater without performance degradation, and a high daily evaporation yield of 15.76 kg m −2 . By eliminating sunlight blocking and guiding condensed vapor, a high clean water collection ratio of 83.5% is achieved. The multiple functionalities make the current nanoarchitectures promising as multipurpose advanced energy materials. Abstract : A one‐step plasma‐enabled deposition is used to produce on‐surface waterways by integrating hydrophilic an on‐surface light absorber and a hydrophobic internal thermal insulator into a solar desalination device, achieving high solar‐vapor efficiency, high daily evaporation yield, a high clean water collection ratio, self‐cleaning and anti‐salt‐fouling behavior and long‐term stability.